PERAN GURU AGAMA ISLAM TERHADAP PEMBENTUKAN AKHLAK PESERTA DIDIK DI MTs AL HIDAYAH GOSARI UJUNGPANGKAH GRESIK - Farihatussinah Farihatussinah; Abdul Jalil; Zuhkhriyan Zakaria (VICRATINA, 2022)
The role of Islamic religious teachers in education plays a strong role in shaping the religious character of students, it can be interpreted that character occurs not because of innate, does not come alone, but must be formed and instilled consciously in students. In the process of moral formation, students will not take place by themselves, but through a process. One of the processes that can shape the character of students is one of them through the role of Islamic religious teachers in schools. This study aims to describe the role of Islamic religious teachers on the moral formation of students at Madrasah Tsanawiyah Al-Hidayah, with 4 research focuses including: (1) Knowing the conception of Islamic education in relation to the moral formation of students, (2) knowing the conception of the role of Islamic religious teachers on the moral formation of students (3) Knowing the factors that influence the formation of students' morals (4) and Knowing what efforts are made by Islamic Religion Teachers in shaping the morals of students at MTs Al Hidayah Gosari Ujungpangkah Gresik. This research is a qualitative research by taking the background of MTs Al Hidayah. Data collection methods used are observation, interviews and documentation. The data sources for this study were the principal of MTs Al Hidayah and religious teachers at MTs Al Hidayah.